Potensi Makanan Lanting sebagai Motor Penggerak Ekonomi Perempuan di Desa Satriyan - Annisaturrakhillah Firdaus; Anisa Zulfa S.A. Noor; Zulvia Arifatun Nisa; Bintang Rifqy Algamar; Alifya Nur Faizah; Adeni Adeni (Lembaga Pengembangan Kinerja Dosen, 2024)
Cassava is a traditional food that has high cultural value in Indonesia. This research was conducted to increase the use of cassava as an ingredient in traditional food products with environmentally friendly packaging. This cassava processing makes a unique and typical traditional food in Satriyan Village, namely lanting or lengko kriyik. The focus of this research is the study of the process of processing cassava into a lanting snack. In this modern era, lanting made from cassava is facing challenges from changes in consumption patterns and competition from the snack industry. However, this traditional food continues to survive and conservation efforts by local communities continue to promote the uniqueness and authenticity of cassava lanting. With these efforts, the cassava plant is not only maintained as a traditional food but also needs to be promoted as one of Indonesia's culinary treasures that should be preserved.